2023
DOI: 10.1590/1519-6984.273404
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and production of sugar-apple under water stress and application of proline

Abstract: The objective of this study was to evaluate the physiology and production of sugar-apple as a function of irrigation intervals and foliar application of proline under the conditions of Paraíba’s semi-arid region. A randomized block design was laid out in a 4 × 2 factorial scheme, with treatments resulting from the combination of four irrigation intervals (1, 4, 8 and 12 days) and two concentrations of proline (0 and 10 mM), with four replicates, and the plot consisted of four usable plants. Increase in irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…One promising strategy is the foliar application of proline, a low-molecular-weight cyclic amino acid known as a key osmoprotectant. Experimental evidence has shown that proline can enhance salinity tolerance in plants, preserving cell membrane integrity and stabilizing enzymes/proteins (Zhu et al, 2020;Torres et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…One promising strategy is the foliar application of proline, a low-molecular-weight cyclic amino acid known as a key osmoprotectant. Experimental evidence has shown that proline can enhance salinity tolerance in plants, preserving cell membrane integrity and stabilizing enzymes/proteins (Zhu et al, 2020;Torres et al, 2023).…”
Section: Introductionmentioning
confidence: 99%